Avaliação escolar na abordagem temática: conhecimentos, práticas e suas relações cognoscentes-epistemológicas - Pereira, Diuliana Nadalon (2024)
School assessment is a topic that has been little studied in the field of Science Education, including the domain of Thematic Approach (TA). In view of this, we investigated “how school evaluation has been understood and applied within the context of TA.” To this end, this qualitative, bibliographic, and participant research was analyzed based on Ludwik Fleck’s epistemology and through Discursive Textual Analysis. In the investigative process, we analyzed academic productions, which led to the emergence of two categories: i) criticisms of evaluation under the logic of banking education; and ii) conceptions and purposes of evaluation in TA. The results show that the studies reflect on contradictions and the need to overcome them, as well as indicate assumptions for building evaluations within TA. In summary, at this stage, we identified the novelty of the thesis, evaluation as a form of silencing, and the extension of TA’s Thought Style. Thus, we highlighted key subjects and contexts in the process of producing and disseminating this perspective. Through the development of a Focus Group and a Formative Process, three categories emerged. In “essential conditions for evaluation in TA: a look at its structural characteristics,” we unveiled that these conditions are based on emancipatory evaluation, as they present elements common to the perspective yet more specific. In “what has limited evaluations aligned with TA?”, we emphasized challenges such as the insufficient circulation of the theme within the Thought Collective. This insufficiency does not represent an absence of knowledge and practices but a boundary-situation for the Thought Collective. Another obstacle is the lack of adequate time and space for implementing the proposals. In “the three dimensions of the evaluative process in TA: knowledge, values, and sociopolitical actions,” we identified that evaluations should foster advancements in these three areas. Overall, we observed a prioritization of knowledge over the other dimensions, which is inconsistent with TA, as understanding and overcoming real-world problems requires the development of values and sociopolitical actions. In this sense, we recognize the need to include these dimensions in teaching-evaluation planning and highlight the potential of articulating with various social actors as sources for generating these dimensions, since schools alone are insufficient to develop them. We also identified cognitive and epistemological relationships between the dimensions, assuming that they present distinct levels and sublevels of criticality, which intersect and incorporate new elements. The final stage of the investigation consisted of examining the use of evaluative processes based on these three dimensions in TA’s different strands and nuances. In summary, we envision broader circulation of ideas on the topic, fostering deeper knowledge and practices and aligning the goals of TA with those of evaluation. Finally, we emphasize the urgency of changes in educational public policies, particularly those related to curricula and teacher appreciation, as well as a greater focus on evaluation in initial and ongoing teacher training.